Organic synthesis and molecular engineering - Nielsen, Mogens Br{uE933}ted. (Hoboken, New Jersey : Wiley, 2014)
'This book focuses on how smart, functional organic molecules are rationally designed and prepared - an area of intense worldwide research, both in academia and industry. It helps guide chemists to choose among key structural units for accomplishing a desired function of a molecule, aggregate, or material. The applications chemists use organic molecular engineering for cut across disciplinary boundaries and include drug delivery, artificial enzymes, conducting materials, molecular electronics, sensors, and molecular machines. The opening chapters cover the concepts, molecular building blocks, and synthetic tools. These are followed by chapters on molecular electronic, supramolecular chemistry and self-assembly, grapheme, and the engineering of photoresponsive materials'--
'This book focuses on how smart, functional organic molecules are rationally designed and prepared - an area of intense worldwide research, both in academia and industry'--
Machine generated contents note: Acknowledgements List of Authors Chapter 1 Introduction Mogens Br{uE933}ted Nielsen Chapter 2 Organic Building Blocks for Molecular Engineering Kasper Lincke and Mogens Br{uE933}ted Nielsen Chapter 3 Design and Synthesis of Organic Molecules for Molecular Electronics Karsten Jennum and Mogens Br{uE933}ted Nielsen Chapter 4 Carbon Nanotubes and Graphene Helena Grennberg Chapter 5 H-Bond Based Nanostructuration of Supramolecular Organic Materials Tomas Marangoni and Davide Bonifazi Chapter 6 Molecular Systems for Solar Thermal Energy Storage and Conversion Kasper Moth-Poulsen Chapter 7 Strategies to Switch Fluorescence with Photochromic Oxazines Erhan Deniz, Janet Cusido, Massimiliano Tomasulo, Mutlu Battal, Ibrahim Yildiz, Marco Petriella, Mariano L. Bossi, Salvatore Sortino, and Fran{u3A73}co M. Raymo Chapter 8 Supramolecular Redox Transduction: Macrocyclic Receptors for Organic Guests Sebastien Goeb, David Canevet, and Marc Salle Chapter 9 Detection of Nitroaromatic Explosives Using TTF-Calix[4]pyrroles Karina R. Larsen, Kent A. Nielsen, Jonathan L. Sessler, and Jan O. Jeppesen Chapter 10 Recognition of Carbohydrates Martina Cacciarini Chapter 11 Cyclodextrin Based Artificial Enzymes -- Synthesis and Function Christian Marcus Pedersen and Mikael Bols Chapter 12 Organozymes: Molecular Engineering and Combinatorial Selection of Peptidic Organo and Transition Metal Catalysts Morten Meldal Chapter 13 Dendrimers in Biology and Nanomedicine JrnBolstad Christensen Chapter 14 Dynamic Combinatorial Chemistry Brian Rasmussen, Anne S{u296E}sen, Sophie R. Beeren, and Michael Pittelkow Index .
Includes bibliographical references (p. 429-436) and index.
Keywords: Physical organic chemistry; Organic compounds -- Synthesis; Molecular structure; Biomolecules